The Effect Of Growing Natural Growth (Zpt) In Growth And Plant Production Of Okra (Abelmoschus Esculentus) - Al Machfudz WDP; Ulfa Suci Rachmawati (Universitas Muhammadiyah Sidoarjo, 2017)
The purpose of this study is, to determine the effect of the Natural Growth Regulatory Agent on the growth and production Okra. This research was conducted in April-July 2017 in Waung Village, Krembung Sub-district, Sidoarjo Regency. This experiment was conducted by single factor experiment which was arranged in a randomized block design with 3 replications with 6 treatment doses of 50 gram / liter, 100 gram / liter, 150 gram / liter, 200gram / liter, and 250 gram / liter. The data obtained from this study were analyzed statistically by using the analysis of variance (ANOVA), if from the analysis of variance there are results that show the real difference, it will be tested further by using the comparison test of Real Beda Jujur (BNJ) with the level of 5% and continued with regression and correlation to determine the influence of factor and variable relationships in the perusal. The results obtained show that in the parame- ters of Plant High, Number of Branches, Diameter, Weight of Wet Fruit and Dry Weight of Fruit there is a real difference. At a dose of 250gram / liter concentration yielding 0.25 M has the best result.vc